Global Indicators Analysis and Consultancy Experience Insights into Correlation between Entrepreneurial Activities and Business Environment - Jovan Krivokapić; Ondrej Jaško (Amfiteatru Economic Journal, 2015)
Many researches and practical experiences clearly indicate the existence of a strong relationship between entrepreneurial activities and the business environment in which these activities are initiated. Although this topic has been quite ignored until the late twentieth century, a lot of studies and consulting practice have contributed to the fact that there are now a number of theories concerning mentioned correlation. These theories aim to offer a model that would provide better utilization of the possibilities from the business environment which could be very important for the development from both macroeconomic and microeconomic aspects. An increasing number of articles on this topic says enough about its importance, and numerous researches by many reputable globally recognized institutions go in favor of this claim. There are many indicators that observe the economic situation in a country or a region from different aspects, so the analyses of these indicators make it possible to determine the specific relationships between entrepreneurial activities and the local and the global business environment. Given the complexity of these relations, the impact cannot be observed partially, without taking into consideration other important factors, but more detailed analyses, however, result in some useful conclusions, which in the proper context can have a positive impact on many economic factors. It is very important to emphasize the fact that the correlation between the business environment and entrepreneurial activities is bidirectional, since this influence is mutual, so that changes in one of these factors can and usually cause some modifications in the other. Frequent series of such iterations actually lead to changes in the business environment, while entrepreneurial activity changes its shape and affects the economy of a country or a region, which is of particular importance for its competitiveness in the era of globalization.
Keywords: L26; M20; E20; E32; 330; entrepreneurship; business environment; consultancy experience-based theories; global performance indicators